Hormetic Concentrations of Hydrogen Peroxide but Not Ethanol Induce Cross-Adaptation to Different Stresses in Budding Yeast - Halyna M. Semchyshyn (International Journal of Microbiology)
The biphasic-dose response of microorganisms to hydrogen peroxide is a phenomenon of particular interest in hormesis research. In different animal models, the dose-response curve for ethanol is also nonlinear showing an inhibitory effect at high doses but a stimulatory effect at low doses. In this study, we observed the hormetic-dose response to ethanol in budding yeast S. cerevisiae. Cross-protection is a phenomenon in which exposure to mild stress results in the acquisition of cellular resistance to lethal stress induced by different factors. Since both hydrogen peroxide and ethanol at low concentrations were found to stimulate yeast colony growth, we evaluated the role of one substance in cell cross-adaptation to the other substance as well as some weak organic acid preservatives. This study demonstrates that, unlike ethanol, hydrogen peroxide at hormetic concentrations causes cross-resistance of S. cerevisiae to different stresses. The regulatory protein Yap1 plays an important role in the hormetic effects by low concentrations of either hydrogen peroxide or ethanol, and it is involved in the yeast cross-adaptation by low sublethal doses of hydrogen peroxide.